Challenges to the implementation of guidance and counseling program in secondary schools of Tigray regional state, Ethiopia - Abay, Alemat; Adane, Kibrom; G.her, Teklay (Evaluation and program planning, 2025)
The purpose of this study was to investigate the factors challenging the implementation of guidance and counseling program in secondary schools of Tigray as perceived by Students and Teachers. The study was a descriptive survey design. By using a self-response questionnaire, data were collected from a sample of 738 (334 Teachers and 404 Students) drawn from the target population of 1888 Teachers and 51291 Students, respectively. Stratified sampling design ending up with simple random sampling was used to select the sample subject. With the help of SPSS 20, the collected data were analyzed by using frequency, percentage, graphs, Mean & standard deviation, and t-test. The findings revealed that the Guidance and Counseling program in the schools was observed to have been challenged with deficiencies in: the Counselor’s competency & professional Ethics; Office Setting (Physical & Psychological); Students’ Perception & Awareness of the service; Support & Awareness by Teachers & school Leaders; and Time (Adequacy & Schedule). In addition, the Teachers’ and Students’ Awareness on: the presence of the guidance and counseling service; types of service available in the center; and benefits of the service to students were revealed to significantly explain the perceptions they hold concerning the role of guidance and counseling service. Further, about half of the Teachers and 66.34 % of the Students were found holding Medium to Low level of perception scores on the role of guidance and counseling service. Thus, it was concluded that the Schools’ guidance and counseling program was not in a position of supporting students in alleviating problems related to academic, vocational, social, and personal/emotional matters. •For students' needs demand a structured school counselling program, guidance and counselling services are vital in secondary education.•The study explored barriers to effective program implementation.•Key challenges include counsellor competence and office conditions.•Poor awareness among teachers and students limits the usage of the counselling service.•Teachers' and students' perceptions of the program role shape its effectiveness.